The Effect of Responsiveness and Assurance of Nurses on Patient Satisfaction in the Emergency RSU UKI - Lia Idealistiana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The nursing field needs to be more professional because people are becoming more picky about the health services they want.  Service providers need to make sure their customers are happy, especially when it comes to emergency services. This can be judged by a number of things, such as how quick and confident nurses are with their services.  How the community sees a hospital can depend on how happy its patients are.  The way the hospital grows will be affected by how few patients are happy with their care.  The number of visits will be affected by how unhappy patients are with health services.  One way to measure how well a hospital is doing at giving health care is by how happy its patients are.  The goal of this study is to find out how the response and confidence of nurses in the Emergency Room of the UKI General Hospital in 2022 affects how happy patients are. Methods: This study is of the analytical type and uses a cross-sectional methodology.  The people in the study were all 5,201 people who went to the Emergency Room at the UKI General Hospital in Jakarta.  Using the Slovin method, a sample of 84 people was taken. Using the accidental sampling technique, a sample of 77 people was then taken.  Chi Square is used to analyze data with single and bivariate tests.  Results: According to the findings, nurse services comprised responsiveness (87.0%) and safe assurance (89.6%), and respondents were happy with nursing care (88.3%). Conclusion: In the IGD Room of the UKI General Hospital in Jakarta, there is a significant relationship between nurse responsiveness (responsiveness) and patient satisfaction (p-value 0,000 0,05).  In the IGD Room of the UKI General Hospital in Jakarta, there is a strong relationship between nurses (assurance) and patient satisfaction (p-value 0,000 0,05).